Persepsi Petani Jagung pada Kinerja Penyuluh Pertanian di Desa Isimu Selatan Kecamatan Tibawa Kabupaten Gorontalo - Angga Septian Fitra Harianto; Amir Halid; Yuriko Boekoesoe (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to determine corn farmers' perceptions of agricultural extension workers in Isimu Selatan Village, Tibawa District, Gorontalo Regency. The research employed a quantitative method, with a sample of 30 respondents determined using Slovin's formula. Data analysis was conducted using the Likert scale approach. The results show that the facility indicator had an average percentage score of 74.66%, which is included in the good category. The indicator for the meeting schedule between corn farmers and field extension workers had an average percentage score of 78.33%, also categorized as good. The indicator for media use by agricultural extension workers had an average percentage score of 90.66%, classified as very good. The indicator for the intensity of extension services had an average percentage score of 90%, also considered very good. Lastly, the indicator for the agricultural extension materials had an average percentage score of 83%, which is categorized as very good.